2013
DOI: 10.1111/bph.12111
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fatty acid amide hydrolase activates Nrf2 signalling and induces heme oxygenase 1 transcription in breast cancer cells

Abstract: BACKGROUND AND PURPOSE Endocannabinoids such as anandamide (AEA) are important lipid ligands regulating cell proliferation, differentiation and apoptosis. Their levels are regulated by hydrolase enzymes, the fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MGL). Here, we investigated whether FAAH or AEA are involved in NF (erythroid-derived 2)-like 2 (Nrf2)/antioxidant responsive element (ARE) pathway. EXPERIMENTAL APPROACH The aim of this study was to analyse the effects of AEA or FAAH inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 73 publications
4
18
0
Order By: Relevance
“…Consistent with this, this study demonstrated that scopolamine significantly increased lipid peroxidation in the brain, while significantly restored by Pal-5HT (1 mg/kg). Probably in support of this, previous report [22] indicated that antioxidant enzymes such as HO-1, GCLC and NQO-1 were remarkably induced by Pal-5HT through Nrf2 activation via PI3K/Akt or p-38 MAPK signaling pathways, irrespective of cannabinoids receptor activation in HT-22 cells challenged with glutamate. From these, it is suggested that the Pal-5HT-mediated restoration of cognitive function may be related primarily to its antioxidant action, as well evidenced from the suppression of scopolamine-induced oxidative damage in brain tissue.…”
Section: Accepted Manuscriptsupporting
confidence: 79%
See 2 more Smart Citations
“…Consistent with this, this study demonstrated that scopolamine significantly increased lipid peroxidation in the brain, while significantly restored by Pal-5HT (1 mg/kg). Probably in support of this, previous report [22] indicated that antioxidant enzymes such as HO-1, GCLC and NQO-1 were remarkably induced by Pal-5HT through Nrf2 activation via PI3K/Akt or p-38 MAPK signaling pathways, irrespective of cannabinoids receptor activation in HT-22 cells challenged with glutamate. From these, it is suggested that the Pal-5HT-mediated restoration of cognitive function may be related primarily to its antioxidant action, as well evidenced from the suppression of scopolamine-induced oxidative damage in brain tissue.…”
Section: Accepted Manuscriptsupporting
confidence: 79%
“…Meanwhile, cannabinoids, lipid mediators in nervous systems [20], have been observed to show anti-inflammatory or anti-allergy activities [21,22]. Recently, phenolic cannabinoids such as N-acyl dopamines or N-arachidonoyl 5-hydroxytryptamine (5HT), present in the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 brain as well as other tissues, were reported to show anti-inflammatory and immunosuppressive action [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agents with the potential to intervene in multiple injuries would offer a novel therapeutic strategy for stroke/cerebral ischemia (4,5). Endocannabinoid AEA can protect neurons from damages through intervening in multiple injuries, such as inhibiting glutamate release (19 -21), scavengering free radicals (6,22,23), reduc ing Ca 2+ influx (24,25), and decreasing inflammatory response (8). However, it is difficult to use AEA in clinical practice because it is rapidly degraded (26).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, N -acyl 5HTs were reported to show anti-allergic and anti-inflammatory actions in mast cells or nerve cells [13,14] . Besides, some endocannabinoids were known to induce antioxidant enzymes via the activation of nuclear factor-E2-related factor-2 (Nrf2) pathway [15] . Our recent study showed that N -palmitoyl 5HT remarkably augmented the level of antioxidant enzymes such as heme oxygenase-1 (HO-1), glutamate-cysteine ligase catalytic subunit (GCLC) or NAD(P)H quinine oxidoreductase-1 (NQO-1) via the activation of Nrf2 pathway in HT-22 cells [14] .…”
Section: Introductionmentioning
confidence: 99%